Temporal Evolution of Digestive System Neoplasm in a Brazilian Northeast State (Research, Society and Development, 2022)
Introduction: Neoplasms of the digestive system are considered a public health problem, which continues to increase over the years. Objective: To analyze the temporal evolution of digestive system neoplasms in a northeastern Brazilian state in the period between 2010 and 2019. Methodology: This is a quantitative study, with a descriptive, retrospective, and ecological approach, carried out in the period from 2010 to 2019, from the bases of the Mortality Information System, made available by the Ministry of Health (DATASUS/MS) through TABNET. Results: In the period from 2015 to 2019, the total number of deaths registered in the municipalities by ICD-10 was 3,548, respectively. While the years that obtained lower values were 2010 and 2012 with 257 and 299 deaths, respectively. The highest percentage of the mortality rate between the years was 12.35% between 2015 and 2019 followed by 8.4 % between 2010 and 2012. And between 2013 and 2018 there was the greatest decrease in mortality rate being 12.0% while between 2010 and 2011 the decrease was 7.0%. Were notified in the state of Alagoas in the period under study, 3,548 (X=354.8 ± S= 69.31) deaths by neoplasm of the digestive system. Conclusion: It was evidenced that, in the period from 2010 to 2019, there was a considerable increase in the morbidity and mortality rate by neoplasia of the digestive system in the general population, especially in the elderly.